Case report: Intensive rehabilitation program delivered before and after single-event multilevel surgery in a girl with diplegic cerebral palsy - Crecchi, Alessandra; Tozzini, Alessandra; Benedetti, Roberta; Maltinti, Marco; Bonfiglio, Luca (Frontiers in Neurology, 2024)
Diplegic cerebral palsy (CP) is often associated with musculoskeletal disorders that contribute to worsen walking function. The standard care in these cases is single-event multilevel surgery (SEMLS) followed by rehabilitation. Our aim was to investigate whether a rehabilitation program starting even before SEML could add a benefit with respect to standard postoperative programs considered by previous research.From 2 months before to 13 months after SEMLS (except for the first month after surgery), the participant underwent a motor training focused on ROM exercises with tactile and kinaesthetic feedback. Walking performance, walking capacity, and quality-of-life were assessed before and after SEMLS at different follow-up times.Walking capacity improved 3 months after SEMLS (i.e., earlier than in current literature) and walking performance improved 12 months after SEMLS (instead of simply returning to baseline as previously reported), with a positive impact on quality-of-life.This case suggests that a rehabilitation program starting even before SEMLS could add benefits over walking function and quality-of-life of children with diplegic CP compared to postoperative programs only.